2007
DOI: 10.1007/s10722-007-9288-4
|View full text |Cite
|
Sign up to set email alerts
|

Infraspecific variation of Sechium edule (Jacq.) Sw. in the state of Veracruz, Mexico

Abstract: In this study a morphological and anatomical variation analysis was carried out with leaves and fruits of Sechium edule, collected in the central region of Veracruz, Mexico. The collected fruits were classified in eight groups according to their typical characteristics. The results showed that the phenotypical distinction of the studied infraspecific S. edule complex is related to morphological and anatomical changes in order to improve the adaptive specialization of the different chayote types with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 27 publications
0
34
1
4
Order By: Relevance
“…Sanwal et al (2010) observed a similar morphological diversity in the North-Eastern germplasm of India as that of Kapoor et al (2014) with the length of the fruit (5.70-15.80 cm), diameter (5.2-10.90) and weight (134-406 g) showing maximum variations. In a study conducted by Cadena-Iniguez et al (2008) fruits of Sechium edule were collected in the central region of Veracruz, Mexico, and classified them under eight groups according to their characteristics. The fruit length varied from 3 to 15 cm which is similar as obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Sanwal et al (2010) observed a similar morphological diversity in the North-Eastern germplasm of India as that of Kapoor et al (2014) with the length of the fruit (5.70-15.80 cm), diameter (5.2-10.90) and weight (134-406 g) showing maximum variations. In a study conducted by Cadena-Iniguez et al (2008) fruits of Sechium edule were collected in the central region of Veracruz, Mexico, and classified them under eight groups according to their characteristics. The fruit length varied from 3 to 15 cm which is similar as obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Flanked regions of the microsatellite were isolated from these four DNA libraries by amplification using compound microsatellite primers (AC) 10 or (GA) 10 and the adaptor primer AP2 (5'-CTATAGGGCACGCGTGGT-3') designed from the 48-mer adapter. The amplified fragments were then integrated into a plasmid pGEM-T vector using pGEM-T Easy Kit (Promega); the plasmids were then transferred into Escherichia coli DH5α, according to the manufacturer's instructions.…”
Section: Microsatellite Marker Design and Evaluationmentioning
confidence: 99%
“…A total of 40 clones from the (AC) 10 and 24 clones from the (GA) 10 libraries were randomly chosen based on amplification size (≥500 bp) and were sequenced. Eighteen (45%) and 9 (37.5%) clones, respectively, from each library, had enough sequence length to design two primers between repeat motif and adapter sequences, and they were used to design IP1 and IP2 primers.…”
Section: Design Of Microsatellite Markers For Chayote and Genetic DIVmentioning
confidence: 99%
“…The reported researches of this crop, focused primarily on genetic traits (Cadena, Avendaño, Soto, Ruiz, Aguirre & Arévalo, 2008;Cadena, Arévalo, Ruiz, Aguirre,Soto, Luna & Zavaleta, 2006;Cadena, Arévalo, Avendaño, Ruíz, Soto, Santiago, Acosta, Aguirre, Cisneros & Ochoa, 2007;Cadena, Soto, Torres, Aguiñiga, Ruiz, Rivera, Avendaño & Santiago, 2013), physiological aspects of water relations and gas exchange, in vitro micro-propagation (Abdelnour, Bermúdez, Alvarenga & Rivera (2006); Alvarenga, Abdelnour & Villalobos (2007) and more recently, participative plant breeding (Avendaño, Cadena, Arévalo, Cisneros, Morales & Ruiz, 2014).…”
Section: Introductionmentioning
confidence: 99%